4-Carboxymethyl-8-methyl-7-oxycoumarin substituted zinc, cobalt and indium phthalocyanines: electrochemical and photochemical properties - (:unkn) unknown (WORLD SCI PUBL CO INC, 2013)
In this study, the novel tetra-substituted Zn(II) (3), Co(II) (4) and In(III) acetate (5) phthalocyanines were synthesized by cyclotetramerization reactions of 7-(2,3-dicyanophenoxy)-8-methylcoumarin-4-acetic acid (2) with corresponding metal salts. All the new compounds have been characterized by MALDI-TOF mass, FT-IR and UV-vis spectra, and elemental analysis as well. The electrochemical, in situ spectroelectrochemical and photochemical properties of tetra-substituted Zn(II), Co(II) and In(III) acetate phthalocyanines were also investigated.
Keywords: coumarin; phthalocyanine; zinc(II); cobalt(II); indium(III); electrochemistry; photochemistry; METAL-FREE; METALLOPHTHALOCYANINES; PHOTOSENSITIZERS; SPECTROSCOPY; COMPLEXES; COUMARIN